LEGISLATING AGAINST PERPETUITY: THE LIMITS OF THE LEGISLATIVE BRANCH’S POWERS TO MODIFY OR TERMINATE CONSERVATION EASEMENTS (Utah Environmental Law Review; Vol 29 No 2 (2009), 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Conservation easement laws provide a seemingly perfect legal equation for landowners to perpetually protect their land while circumnavigating both the law’s traditional suspicion of perpetual restrictions on land and the whims of present politics. But as the use of conservation easements continues to grow, and the supply of conservable private land diminishes, the role of organizations holding conservation easements will necessarily change. Over the next twenty years, it is likely that the institutional focus of the land trusts and government entities holding conservation easements will shift from the acquisition of new easements to the stewardship of existing easements. As conservation easements age, and the environmental, political, and social landscape evolves, the pressure to modify or even terminate easements will inevitably grow.